DESIGN TOOL ROOM DOOR ALARM AT89C51 microcontroller - Nenny Anggraini Anggraini (STMIK Jakarta, 2004)
Microprocessor and microcomputer technology is a new technology that is currently beingdeveloped. One of them is a microcontroller technology, which is an application of artificialintelligence material that resembles the concept of the human mind.With a microcontroller, there are many applications that can be used, for example amicrocontroller technology is the sensor, which is used as a tool that can control a sound andlight alarm on a door supervisor. This application is expected to assist the householder inorder to monitor the room where the door was open at night or at certain times.